Direitos reprodutivos, direitos humanos e bioética: repercussões éticas e jurídicas do projeto monoparental feminino - Motta, Kátia Borges (Universidade do Vale do Rio do Sinos, 2007)
The subject concerning reproductive rights, as most of the demands nowadays, is very complex, not only because of its links with biosciences and biotechnology with its particular dynamics and ambiguous effects , but also because of its origins in feminism which makes it very likely to partial and/or partidary interpretations. Therefore, the present dissertation intends to face the issue of reproductive rights taking into consideration its inherent complexity, which is very clear in the chosen example of the single woman project of parenthood in which a single woman, addopting the use of artificial insemination with a donor’s semen, has the intention to form a family composed only by a mother and a child, without establishing affective or sexual bonds with a man. Searching the ethical and juridical consequences that would arise from the single woman project of parenthood, this research starts from two main analysis: a bioethical one, in the first chapter, with emphasis in the principalist and personalist m
Keywords: direitos humanos; direitos reprodutivos; projeto monoparental feminino; bioética; feminism; human rights; reproductive rights; single parenthood; bioethics; Ciências Sociais Aplicadas